1990
DOI: 10.1002/mrm.1910150310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiopulmonary bypass on brain and heart metabolism: A 31P NMR study

Abstract: The development of a large animal preparation using 31P nuclear magnetic resonance (NMR) spectroscopy for the study of cerebral and myocardial metabolism during cardiopulmonary bypass (CPB) is reported. The effect of normothermic CPB on myocardial and cerebral metabolism was evaluated. Adolescent sheep were used which have low levels of 2,3-diphosphoglycerate, a compound which can interfere with the calculation of intracellular pH and inorganic phosphate content. CPB was performed using standard procedures mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The changes caused by the various interventions during the surgical procedure tended to be rapid and short lived. Studies of the effect on brain and tissue metabolism of normothermic cardiopulmonary bypass (as used in our study) did not change high energy phosphate levels or intracellular pH (16). The earliest report of conjunctival pH noted that the conjunctival pH was generally .2 pH units lower than the arterial value (17).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The changes caused by the various interventions during the surgical procedure tended to be rapid and short lived. Studies of the effect on brain and tissue metabolism of normothermic cardiopulmonary bypass (as used in our study) did not change high energy phosphate levels or intracellular pH (16). The earliest report of conjunctival pH noted that the conjunctival pH was generally .2 pH units lower than the arterial value (17).…”
Section: Discussionsupporting
confidence: 43%
“…A prior investigation which measured muscle gastric mucosal oxygen levels during JECT. 2011;43: [13][14][15][16][17][18] CPB showed that tissue oxygenation fell sharply during the initiation of cardiopulmonary bypass and remained significantly below baseline for 3 to 5 hours following the procedure (19). These investigators did not find any relationship between arterial blood gas levels and the tissue pH or oxygen tension.…”
Section: Discussionmentioning
confidence: 97%
“…8 " 10 Experimentally, Watanabe et al" have demonstrated intracellular cerebral hypoxia and acidosis during and after deep hypothermic bypass, most pronounced in animals subjected to circulatory arrest. In a study using magnetic resonance imaging in lambs, Swain et al 12 have demonstrated the lack of recovery of energy stores in the brain after bypass. Most importantly, they demonstrated the association of these findings with poor neurologic outcome.…”
Section: Effect On the Brain Of Heart Surgery In The Youngmentioning
confidence: 99%
“…Data from both humans and animals suggest that these estimates represent a reasonable approximation of acceptable minimal rates of flow during hypothermic bypass. Swain et al 12 have demonstrated that rates of flow of 10 ml«kg~1«min" 1 at 15 °C for periods of up to two hours in eight-week old sheep maintain normal levels of adenosine triphosphate and phosphocreatine, together with normal pH of the brain. When flow is reduced to 5 ml'kg~1»min" 1 at 15 °C, organic phosphates become depleted and the pH of the brain begins to fall.…”
Section: The Phase Of Surgical Intervention Bypass Using Low Flowmentioning
confidence: 99%
“…CBF and CMR02 are reduced below baseline measurements and oxygen extraction does not increase. Animal data suggest that after DHCA the brain is acidotic and hypoxic (Watanabe et al 1991a;Swain et al 1990). With reperfusion, the rate at which the brain recovers ATP, pH and Po2 is markedly delayed when compared with continuous flow CPB.…”
Section: Rewarming Period (Recovery Phase)mentioning
confidence: 99%